Evaluation of demineralized lignin and lignin-phenolic resin blends to produce biocoke suitable for blast furnace operation. (15th December 2019) - Castro-Díaz, Miguel; Vega, María Fernanda; Díaz-Faes, Elvira; Barriocanal, Carmen; Musa, Umaru; Snape, Colin
Highlights: Hydrochar from demineralized lignin is less reactive than that of pristine lignin. The biocoke from demineralized lignin is much more reactive than coke from coal. Phenolic resin can act as binder of torrefied lignin and coal to produce biocoke. The microporosity of the biocoke does not correlate with its reactivity. Abstract: Metallurgical coke makers could reduce carbon emissions and material costs by introducing waste lignin in coke oven charges. Two approaches have been studied here to increase the use of lignin in the preparation of metallurgical coke: lignin demineralization with H2 SO4 and lignin blending with a low rank coal using phenolic resin as binder. The biocoke obtained after carbonization at 1000 °C from the hydrochar of demineralized lignin (350 °C, 6 h, biomass/water = 0.5 wt/wt) had much higher reactivity than the coke obtained from the low rank coking coal, proving that demineralization of lignin prior hydrothermal conversion is not a valid route for biocoke making. In the other approach, it was found that blends containing 70 wt% low rank coal, 24 wt% torrefied lignin (before or after demineralization) and 6 wt% phenolic resin produced biocokes with suitable mechanical strength for handling but higher reactivity than the coke obtained from the low rank coking coal alone. The microporous surface areas of the biocokes studied did not correlate with their reactivity values.